Association of knee OA structural phenotypes to risk for progression: a secondary analysis from the Foundation for National Institutes of Health Osteoarthritis Biomarkers study (FNIH). Issue 9 (September 2020) - Roemer, F.W.; Collins, J.E.; Neogi, T.; Crema, M.D.; Guermazi, A.
Summary: Purpose: Aim was to stratify the knee MRIs of the Foundation for National Institutes of Health Osteoarthritis Biomarkers Consortium (FNIH) cohort into distinct structural phenotypes based on semiquantitative assessment and to determine risk for pain and structural progression over 48 months. Methods: The study sample from the FNIH project was selected as a nested case–control study with knees showing either 1) radiographic and pain progression (i.e., "composite" cases), 2) radiographic progression only ("JSL"), 3) pain progression only, and 4) neither radiographic nor pain progression. MRI was performed on 3T systems. MRIs were read according to the MOAKS scoring system. Knees were stratified into subchondral bone, cartilage/meniscus and inflammatory phenotypes using the baseline visits. The relation of each phenotype to risk of being in the combined JSL plus composite outcome or composite case only group compared to those not having that phenotype was determined using logistic regression. Only KL2 and 3 and those without root tears were included. Results: 485 knees were included. 362 (75%) did not have any phenotype, while 95 (20%) had the bone phenotype, 22 (5%) the cartilage/meniscus phenotype and 19 (4%) the inflammatory phenotype. The bone phenotype was associated with a higher odds of the combined JSL plus composite outcome and composite outcome only (OR 1.81; [95%CI 1.14, 2.85] and 1.65; 95%CI [1.04, 2.61]) while the inflammatory (OR 0.96 [95%CI 0.38, 2.42] and 1.25; 95%CI [0.48, 3.25]) and the cartilage/meniscus phenotypes were not significantly associated with outcome (OR 1.30 95%CI [0.55, 3.07] and 0.99; 95%CI [0.40, 2, 49]). Conclusions: The bone phenotype was associated with increased risk of having both radiographic and pain progression. Phenotypic stratification may be useful to consider when selecting patients for inclusion in clinical trials.